2003
DOI: 10.1021/bi034651u
|View full text |Cite
|
Sign up to set email alerts
|

Quantification and Glucocorticoid Regulation of Glucocorticoid Receptor Transcripts in Two Human Leukemic Cell Lines

Abstract: We have quantified the basal and glucocorticoid-regulated levels of different transcripts from the human glucocorticoid receptor (GR) gene in the T-cell acute lymphoblastic leukemia cell line, CEM-C7, and in the B lymphoblastoid cell line, IM-9. Highly specific quantitative, reverse transcription-polymerase chain reaction assays measured total GR transcripts, transcripts encoding the isoforms glucocorticoid receptor alpha (GRalpha) and glucocorticoid receptor beta (GRbeta), and transcripts containing different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 52 publications
6
70
2
Order By: Relevance
“…However, if this was the case, we would expect that the proportion of GR mRNA containing exon 1 1 would be decreased by glucocorticoids, and this was not apparent even though effects of glucocorticoids upon thymus size and cellularity are significant at 72 h. Third, and most likely, all the mRNA variants may be similarly regulated in all cells. Pedersen and Vedeckis have recently shown that although the magnitude of glucocorticoid regulation of mouse GR mRNA variants (including 1A) differs between variants, the overall direction of regulation (up or down) is dependent on cell type and does not differ between mRNA variants (Pedersen et al 2003). Thus, in vivo, although we cannot rule out differential regulation of promoter activity over the short term (24 h), there is no differential regulation apparent over 72 h.…”
Section: Discussionmentioning
confidence: 66%
“…However, if this was the case, we would expect that the proportion of GR mRNA containing exon 1 1 would be decreased by glucocorticoids, and this was not apparent even though effects of glucocorticoids upon thymus size and cellularity are significant at 72 h. Third, and most likely, all the mRNA variants may be similarly regulated in all cells. Pedersen and Vedeckis have recently shown that although the magnitude of glucocorticoid regulation of mouse GR mRNA variants (including 1A) differs between variants, the overall direction of regulation (up or down) is dependent on cell type and does not differ between mRNA variants (Pedersen et al 2003). Thus, in vivo, although we cannot rule out differential regulation of promoter activity over the short term (24 h), there is no differential regulation apparent over 72 h.…”
Section: Discussionmentioning
confidence: 66%
“…The remaining primers for regular PCR and sequencing were designed with Primer3 software (33) available online. 3 Primers for real-time PCR quantification of promoters 1A1, 1A2, 1A3, 1B, and 1C were identical to previous study (34). The other primers were designed with Primer Express software (Applied Biosystems, Foster City, CA).…”
Section: Methodsmentioning
confidence: 99%
“…There seems to be also a poorly understood statistical link between the 5'UTR and 6 3' splice variants produced. One of the first studies to address this question showed that 7 exon 1A3, and to a lesser extend 1B and 1C contribute most to the expression of GR-α 8 isoform [24]. By comparing the most abundant exon 1 containing transcripts (1A, 1B 1C) 9…”
Section: Gr Transcriptionmentioning
confidence: 99%
“…Page 10 of 32 A c c e p t e d M a n u s c r i p t 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 are more sensitive to GC induced apoptosis, and 1A3-transcripts were shown to be the 7 most GC responsive of all first exons investigated [16,24]. Although 1A containing 8 transcripts correspond to only about 10% of all GR transcripts [42], their contribution to 9 the tissue-specific response to GC treatment was considered essential [16,24].…”
Section: Investigations 22mentioning
confidence: 99%
See 1 more Smart Citation